2020
DOI: 10.1007/s11071-020-05929-4
|View full text |Cite
|
Sign up to set email alerts
|

Global dynamics of a multi-strain SEIR epidemic model with general incidence rates: application to COVID-19 pandemic

Abstract: This paper investigates the global stability analysis of two-strain epidemic model with two general incidence rates. The problem is modelled by a system of six nonlinear ordinary differential equations describing the evolution of susceptible, exposed, infected and removed individuals. The wellposedness of the suggested model is established in terms of existence, positivity and boundedness of solutions. Four equilibrium points are given, namely the disease-free equilibrium, the endemic equilibrium with respect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
74
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(86 citation statements)
references
References 38 publications
0
74
0
1
Order By: Relevance
“…Simulations have been used since the early days of the COVID-19 pandemic. Classic compartmental epidemiological models were first produced (e.g., many SEIR models [21][22][23][24]), with a focus on estimating broad trends and key epidemiological quantities such as the expected number of new cases generated by each infected individual (i.e., the basic reproduction number R 0 ). Such compartmental models provide limited support to study the effect of interventions, for instance by lowering the contact rate to represent the impact of social distancing.…”
Section: Introductionmentioning
confidence: 99%
“…Simulations have been used since the early days of the COVID-19 pandemic. Classic compartmental epidemiological models were first produced (e.g., many SEIR models [21][22][23][24]), with a focus on estimating broad trends and key epidemiological quantities such as the expected number of new cases generated by each infected individual (i.e., the basic reproduction number R 0 ). Such compartmental models provide limited support to study the effect of interventions, for instance by lowering the contact rate to represent the impact of social distancing.…”
Section: Introductionmentioning
confidence: 99%
“…This value helps eliminate the disease and expected number of secondary infections produced by an infected individual in a population when all individuals are susceptible to infection. In [12], authors made a multi-strain-modified SEIR epidemic model for COVID-19 and wrote a complete analysis on how to control the value of the reproduction number to control the next upcoming virus peaks.…”
Section: Introductionmentioning
confidence: 99%
“…Lie et al proposed a data-driven COVID-19 model with distributed delay [ 35 ]. Global dynamics of a COVID-19 SEIR epidemic model has been investigated by Khyar et al [ 36 ]. Further, different authors have suggested control strategies for disease transmission of COVID-19 [ 37 39 ].…”
Section: Introductionmentioning
confidence: 99%